Government and the politics of India - "Thakur, Ramesh" (New Delhi, 1995)
The Government and Politics of India provides a clear and concise account of the contemporary Indian political system. It explains the historical legacies that have shaped the structures of Indian government and influenced the patterns of its politics. It describes the network of Indian institutions at federal and provincial level. It conveys a sense of where power is located, how it is used and the constraints on its exercise. Special attention is devoted to caste, religion and regionalism in Indian society and to the nature of democratic politics in relation to Third World development.
Keywords: India-Politics and government-1995